2019
DOI: 10.1016/j.cell.2018.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of the Electrical Connectome of C. elegans

Abstract: The specific patterns and functional properties of electrical synapses of a nervous system are defined by the neuron-specific complement of electrical synapse constituents. We systematically examined the molecular composition of the electrical connectome of the nematode C. elegans through a genomeand nervous-system-wide analysis of the expression patterns of the invertebrate electrical synapse constituents, the innexins. We observe highly complex combinatorial expression patterns throughout the nervous system … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
210
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(215 citation statements)
references
References 58 publications
5
210
0
Order By: Relevance
“…Innexins are wide expressed in nervous system of C. elegans (Altun et al, 2009;Bhattacharya et al, 2019) to form gap junctions (electrical synapses). Some studies to date reported their implication of neuronal innexins in behavior: unc-9 for aggregation of social behavior (Jang et al, 2017), inx-1 for behavioral components of avoidance behavior (Hori, Oda, Suehiro, Iino, & Mitani, 2018), and unc-9 and unc-7 for bias for forward movement (Kawano et al, 2011) and regulation of sleep (Huang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Innexins are wide expressed in nervous system of C. elegans (Altun et al, 2009;Bhattacharya et al, 2019) to form gap junctions (electrical synapses). Some studies to date reported their implication of neuronal innexins in behavior: unc-9 for aggregation of social behavior (Jang et al, 2017), inx-1 for behavioral components of avoidance behavior (Hori, Oda, Suehiro, Iino, & Mitani, 2018), and unc-9 and unc-7 for bias for forward movement (Kawano et al, 2011) and regulation of sleep (Huang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The human genome contains 21 connexins and 3 pannexins (Penuela, Harland, Simek, & Laird, ; Söhl & Willecke, ), whereas the Caenorhabditis elegans and Drosophila melanogaster genomes have 25 and 8 innexins, respectively (Phelan & Starich, ; Stebbings et al, ). Although in vivo neuronal expressions of innexins are documented comprehensively in C. elegans (Altun, Chen, Wang, & Hall, ; Bhattacharya, Aghayeva, Berghoff, & Hobert, ), their roles in biological processes are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…2). C. elegans gap junctions have a plethora of functions in all organs, with different groups of innexins being expressed in each of them 18,20 .…”
Section: The Effects Of Innexins On Lifespan Correlate With Their Tismentioning
confidence: 99%
“…Neurons are terminally differentiated, yet retain a degree of plasticity to facilitate responses to ephemeral environments and internal metabolic states (Bhattacharya et al, 2019;Cho et al, 2016;Delaney et al, 2017;Gruner et al, 2014;Pocock and Hobert, 2010;Witham et al, 2016). Neuronal plasticity can be mediated through transcriptional changes that alter synapse formation, receptor composition, and signalling molecules (Bayer and Hobert, 2018;Gruner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, however, there is a dearth of knowledge about the transcription factors that define and drive neuronal adaption to nutrient availability. And we are only just beginning to appreciate the extent to which the transcription factors that specify neuronal fates are re-purposed, post-mitotically, to drive adaptive changes in neuronal gene expression (Bhattacharya et al, 2019).…”
Section: Introductionmentioning
confidence: 99%